Analisis Faktor-Faktor yang Mempengaruhi Tingkat Pengangguran Terbuka di Kota Medan: Periode 2017-2022 - Suci frisnoiry; Fayyaza Aliya Nafisa Siregar; Risya Indah Syakira; Salwa Silviyanti Asrizal (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to analyze the factors that influence the level of open unemployment in Medan City during the 2017-2022 period. Variables considered in the analysis include population, minimum wage, and human development index. By using statistical analysis methods, the research results show that these factors have a significant influence on the unemployment rate in Medan City. Apart from that, the determinant test, F test, and T test were also carried out to test the relationship between the variables studied. The findings from this research provide valuable information for policy makers in designing more effective economic development strategies in Medan City. The implications of this research can be used as a basis for formulating policies that can reduce unemployment levels and improve people's welfare in the region.